2015
DOI: 10.1016/j.jcv.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Antibody avidity following secondary dengue virus type 2 infection across a range of disease severity

Abstract: Background The four dengue virus serotypes (DENV1-4) are responsible for the most prevalent mosquito-borne viral illness in humans. DENV causes a spectrum of disease from self-limiting dengue fever (DF) to severe, life-threatening dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS). Antibodies from one infection can contribute to either protection or increased disease severity in a subsequent infection with a distinct DENV serotype. The effectiveness of the antibody response is modulated by both the affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…We can concluded that all infecting serotypes were DENV-3 related to the outbreak in 2009 and all symptomatic persons and asymptomatic individuals were all primary infection. According to previous reports [ 3 9 ], the existence of dengue antibodies could enhance dengue infection and Zika infection. Accordingly, we suggest that more attention should be paid to dengue or zika cases who have been infected with dengue viruses, even they contracted dengue viruses many years ago.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can concluded that all infecting serotypes were DENV-3 related to the outbreak in 2009 and all symptomatic persons and asymptomatic individuals were all primary infection. According to previous reports [ 3 9 ], the existence of dengue antibodies could enhance dengue infection and Zika infection. Accordingly, we suggest that more attention should be paid to dengue or zika cases who have been infected with dengue viruses, even they contracted dengue viruses many years ago.…”
Section: Discussionmentioning
confidence: 99%
“…DENV cause a spectrum of diseases ranging from subclinical manifestations or a mild, self-limiting disease, dengue fever (DF), to a more severe disease, dengue hemorrhagic fever (DHF), which can progress to dengue shock syndrome (DSS) and death. Previous studies reported that cross-reacting antibodies enhanced dengue infection in humans and antibody dependent enhancement (ADE) had been proposed as the early mechanism underlying DHF/DSS [ 3 7 ]. Moreover, recent studies have reported that human antibody responses after dengue virus infection were highly cross-reactive with Zika virus and was able to drive ADE of Zika infection [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that antibody avidity correlates with a neutralizing capacity in natural infections of human by dengue virus 46 . Moreover, an increased severity of dengue diseases is associated with a lower antibody avidity at later time-points after infection 47 . Therefore, antibody avidity should be an important index to evaluate vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in disease severity was observed when the interval between first and second infections was 20 years as opposed to 4 years 30 . As an explanation, it was observed that severe disease at a long interval was correlated with an observed steady decrease in heterotypic antibody titers over a long period 37, 38 . During secondary dengue infections, adults are at greater risk than children of bleeding whereas children are at greater risk than adults of vascular permeability 39 .…”
Section: Clinical Responsesmentioning
confidence: 99%